2008
DOI: 10.1152/japplphysiol.00915.2007
|View full text |Cite
|
Sign up to set email alerts
|

AMPK activation attenuates S6K1, 4E-BP1, and eEF2 signaling responses to high-frequency electrically stimulated skeletal muscle contractions

Abstract: Regulation of protein translation through Akt and the downstream mammalian target of rapamycin (mTOR) pathway is an important component of the cellular response to hypertrophic stimuli. It has been proposed that 5'-AMP-activated protein kinase (AMPK) activation during muscle contraction may limit the hypertrophic response to resistance-type exercise by inhibiting translational signaling. However, experimental manipulation of AMPK activity during such a stimulus has not been attempted. Therefore, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
99
4
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 57 publications
10
99
4
4
Order By: Relevance
“…Therefore, it seems that MAPK may not be activated due to ROS deprival although the correlation of ROS levels with MAPK activity and MAPK gene expression is yet to be identified in yeast. On the other hand, it is accepted that protein kinases are implicated in yeast longevity [19,29,39,40], we actually observed the significant upregulation of Tor1 in PME yeast cells, which is as same as the case described in fission yeast [41]. It is unclear, however, whether the upregulation of Tor1 is due to the inhibition of Tor1p per se upon exposure of yeast cells to CR, ART, or H 2 O 2 .…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, it seems that MAPK may not be activated due to ROS deprival although the correlation of ROS levels with MAPK activity and MAPK gene expression is yet to be identified in yeast. On the other hand, it is accepted that protein kinases are implicated in yeast longevity [19,29,39,40], we actually observed the significant upregulation of Tor1 in PME yeast cells, which is as same as the case described in fission yeast [41]. It is unclear, however, whether the upregulation of Tor1 is due to the inhibition of Tor1p per se upon exposure of yeast cells to CR, ART, or H 2 O 2 .…”
Section: Discussionsupporting
confidence: 84%
“…We interpret duty cycle as primarily a metabolic stimulus, dependent on substrate depletion, and oriented at restoring the energy balance. High duty cycles are common among studies of HFC-induced signaling, and groups using protocols similar to HDC-long also report increased ACC phosphorylation (Thomson et al, 2008) and reduced glycogen content (Nader and Esser, 2001;Russ, 2008), although the reduction in glycogen appears to be greater in rats (Nader and Esser, 2001) than in mice (present study). Force measurements also indicate that HDC imposes higher metabolic load.…”
Section: P38-mtor Signaling After Hfesmentioning
confidence: 44%
“…AMPK knockout mice demonstrate elevated p70S6k T389 phosphorylation, protein synthesis and fiber size (Lantier et al, 2010). Artificial activation of AMPK by AICAR diminishes contraction-induced mTORC1 signaling, decreases protein synthesis and induces atrophy in myotubes and muscle (Bolster et al, 2002;Deshmukh et al, 2008;Thomson et al, 2008). However, in kinase-dead AMPKα2 mice, running induces exaggerated phosphorylation of ERK1/2 (Maarbjerg et al, 2009), and AICAR treatment activates p38 (Lemieux et al, 2003), indicating substantial interaction among AMPK and MAPK pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Multisite phosphorylation of the translational repressor 4E-BP1 results in its dissociation from eIF4E, thereby allowing eIF4E to assemble with eIF4G, facilitating the recruitment of other translation initiation factors to form the eIF4F complex and initiate cap-dependent translation (16). Previous studies showed elevated 4E-BP1 phosphorylation after resistance exercise (4,38). However, changes in phosphorylation of 4E-BP1 and p70S6K in response to a bout of exercise do not necessarily correspond, and some previous studies have failed to find elevated phosphorylation of 4E-BP1 (9,10,23,29).…”
Section: Discussionmentioning
confidence: 95%